The effect of own capital rentability, solvability, profitability and liquidity on dividend policy in food and beverage sub sector companies listed on Indonesia Stock Exchange (IDX) - Wartoyo Hadi (The Management Journal of Binaniaga, 2019)
The aims of study to determine the effect of rentability of own capital, solvability, Profitability and Liquidity on dividend policy. The population of this study is all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017 as many as 18 companies. While the sample is determined using the purposive sampling method. Companies that meet the criteria are only 7 companies. To analyze the data used multiple linear regression methods. The results of research, own capital rentability and current partial ratio (CR) has a negative and significant effect on the dividend payout ratio. Meanwhile, debt to equity ratio (DER) and return on assets (ROA) partially have a positive and significant effect on the dividend payout ratio. The results of the F-test show that the variable profitability of own capital rentability, solvency, profitability and liquidity simultaneously influence dividend policy. Keywords: own capital rentability, debt to equity ratio, return on asset, current ratio, dividend payout ratio.